Solidifiable inorganic plugging agent for fractured leakage and preparation method thereof

By developing a specific crack leakage loss-free solidification inorganic leak plugging agent, the problem of low leakage plugging success rate in crack formation wells is solved, and an efficient and safe leak plugging effect is achieved.

CN119775982APending Publication Date: 2025-04-08CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311285943.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When existing leak plugging agents are used in cracked formation wells, the leak plugging success rate is low, and it is easy to lead to complex and risky underground.

Method used

A crack leakage loss-coolable inorganic leakage plugging agent has been developed. The raw materials include water retention agent, suspension agent, consolidation material and regulator. It is prepared by specific ratio and stirring methods to form a product that is prone to enter the leakage channel.

Benefits of technology

The leak plugging agent is prone to entering the leaking channel, with a large static shear force and strong water retention ability. It can effectively plug the leaking channel and avoid repeated leakage. The compressive strength after solidification is low, avoiding the problem of drilling a new wellbore during drilling plugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic plugging agents, in particular to a solidifiable inorganic plugging agent for fractured leakage and a preparation method thereof.The solidifiable inorganic plugging agent for fractured leakage comprises the following raw materials: a water-retaining agent, a suspending agent, a solidifying material, a conditioning agent and the balance of water. And adding the suspending agent and the consolidation material, and uniformly stirring. The solidifiable inorganic plugging agent for fractured leakage easily enters a leakage channel and space, is small in density, large in static shearing force, high in water retention capacity and capable of being solidified, once plugging succeeds, the risk of re-leakage does not exist, meanwhile, the compressive strength is low after solidification, the problem that a new well is drilled during plug drilling does not exist, and the plugging agent has the good application prospect. And the problems of well collapse and drill jamming caused by drilling a new borehole are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic plugging agents, in particular to a solidifiable inorganic plugging agent for fracture leakage and a preparation method thereof. Background Art

[0003] At present, the success rate of one-time plugging of leakage in fractured formations at home and abroad is low. Loss in fractured formations has become a global problem that restricts the progress of oil and gas exploration and development. Improving the success rate of one-time plugging of leakage in fractured formations is an urgent need for oil fields around the world to ensure "safe, efficient and economical" drilling.

[0004] At present, the main plugging agents can be classified into three categories according to the plugging mechanism: bridge plugging, cement consolidation, and high filtration loss: 1. Bridge plugging: It is a compound of various materials and is a commonly used plugging agent on site. It is mainly used for small leakage. The advantage is low cost. The disadvantage is that the particle size of the material must match the leakage channel to successfully plug the leakage. If the particle size is too small, it will leak directly into the formation, and if it is too large, it will directly seal the door, so the success rate is low and it is easy to leak again; 2. Cement consolidation type: It is composed of cement, water and admixtures, with a simple formula and easy construction. If the plugging agent can be retained in the leakage channel, the plugging is successful. However, cement slurry is easily diluted by the fluid in the leakage channel, so the success rate on site is low; once the plug is successfully left in the inclined well, it is easy to drill a new wellbore when drilling the plug, leaving a crescent-shaped cement ring in the wellbore. When drilling continues, the drill bit hits the well wall, causing the cement ring to be damaged and fall off, resulting in drill jam; 3. High filtration loss type: This plugging agent enters the leakage channel in a fluid state, accumulates and loses in a narrow position, and then forms a plugging section. In field applications, it often forms an accumulation at the channel mouth, or directly flows into the deep formation and cannot form an effective plugging section, so the success rate is low.

[0005] In general, existing plugging agents are mainly used to treat small leaks in high-permeability formations, and are less suitable for fracture leaks. The plugging success rate is low. Although cement slurry can achieve certain effects, it is easy to cause new underground complexities and risks. Summary of the invention

[0006] The present invention provides a solidifiable inorganic plugging agent for fracture leakage and a preparation method thereof, which overcomes the deficiencies of the above-mentioned prior art and can effectively solve the problem of low plugging success rate of the existing plugging agents.

[0007] One of the technical solutions of the present invention is achieved through the following measures: a solidifiable inorganic plugging agent for fracture leakage, the raw materials of which include 4% to 5% water retaining agent, 3.5% to 4.5% suspending agent, 10% to 20% consolidating material, 0.1% to 0.5% regulator and the balance water by weight.

[0008] The following are further optimizations and / or improvements to the above technical solutions: The water retaining agent is 2-acrylamide-2-methylpropanesulfonic acid copolymer.

[0009] The above-mentioned suspending agent is one or more of sepiolite powder, vermiculite powder and basalt fiber.

[0010] The above-mentioned consolidation material is crystalline glassy tuff powder with a particle size of 1000 mesh to 1200 mesh.

[0011] The above-mentioned regulator is sodium hydroxide.

[0012] The solidifiable inorganic plugging agent for fracture leakage is obtained by the following method: add the required amount of water retaining agent and regulator to the required amount of water and stir evenly, then add the required amount of suspending agent and consolidating material and stir evenly to obtain the solidifiable inorganic plugging agent for fracture leakage.

[0013] The second technical solution of the present invention is achieved through the following measures: a preparation method of a solidifiable inorganic plugging agent for fracture leakage, which is carried out according to the following method: adding a required amount of water-retaining agent and a regulator to a required amount of water and stirring evenly, then adding a required amount of a suspending agent and a consolidating material and stirring evenly to obtain a solidifiable inorganic plugging agent for fracture leakage.

[0014] The solidifiable inorganic plugging agent for fracture leakage of the present invention can easily enter the leakage channel and space, has low density, large static shear force, strong water retention capacity, and can solidify itself. Once the plugging is successful, there is no risk of re-leakage. At the same time, its compressive strength after solidification is low, and there is no problem of drilling a new wellbore when drilling the plug, thus avoiding the problem of well collapse and drill jamming caused by drilling a new wellbore. DETAILED DESCRIPTION

[0015] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions in which the solvent is water, for example, the hydrochloric acid solution is an aqueous hydrochloric acid solution.

[0016] The present invention will be further described below in conjunction with embodiments: Example 1: The solidifiable inorganic plugging agent for fracture leakage comprises, by weight, 4% to 5% of a water retaining agent, 3.5% to 4.5% of a suspending agent, 10% to 20% of a consolidating material, 0.1% to 0.5% of a regulator and the balance of water.

[0017] Example 2: As an optimization of the above example, the water retaining agent is 2-acrylamide-2-methylpropanesulfonic acid copolymer.

[0018] In the present invention, the raw material water retaining agent is selected from 2-acrylamide-2-methylpropane sulfonic acid copolymer AMPS, the main chain of the molecule is a carbon chain structure, the thermal stability is very high, the 2-methylpropane sulfonic acid side group can enhance the rigidity of the molecular chain, improve the thermal stability, and at the same time, the hydrolysis of its amide group can be suppressed within a certain range, and the stability of the 2-acrylamide-2-methylpropane sulfonic acid group can be improved. Even if there is a situation of partial hydrolysis, the hydrolysis makes the group hydrophobic, and the hydrophobic association can also be generated at the same time, so that the 2-acrylamide-2-methylpropane sulfonic acid can still maintain good stability. The effect of the copolymer is to protect the components in the suspension of the solidifiable inorganic plugging agent for fracture leakage from being dispersed and diluted by the external fluid, so that the solidifiable inorganic plugging agent for fracture leakage is solidified according to the required time.

[0019] Embodiment 3: As an optimization of the above embodiment, the suspending agent is one or more of sepiolite powder, vermiculite powder and basalt fiber.

[0020] In the present invention, the suspending agent is selected from sepiolite powder, vermiculite powder or basalt fiber, and its function is to disperse in water, increase the viscosity and shear force of the liquid, so that the suspension of the solidifiable inorganic plugging agent for fracture leakage has a stable state without water precipitation, and at the same time has a high static shear force, forcing the suspension of the solidifiable inorganic plugging agent for fracture leakage to be easily retained in the leakage channel.

[0021] Example 4: As an optimization of the above example, the consolidation material is crystalline glass tuff powder with a particle size of 1000 mesh to 1200 mesh.

[0022] In the present invention, the consolidation material is selected from crystal glass tuff powder with a particle size of 1000 mesh to 1200 mesh, and its function is to react chemically with the regulator to turn the plugging agent suspension into a solid, plug the leakage channel, and achieve the purpose of plugging.

[0023] Embodiment 5: As the optimization of the above embodiment, the regulator is sodium hydroxide.

[0024] In the present invention, the regulator is sodium hydroxide, which has the function of chemically reacting with the consolidation material to turn the plugging agent suspension into a solid, plugging the leakage channel and achieving the purpose of plugging.

[0025] Example 6: As an optimization of the above example, a solidifiable inorganic plugging agent for fracture leakage is obtained by the following method: add the required amount of water retaining agent and regulator to the required amount of water and stir evenly, then add the required amount of suspending agent and consolidating material and stir evenly to obtain a solidifiable inorganic plugging agent for fracture leakage.

[0026] Embodiment 7: The solidifiable inorganic plugging agent for fracture leakage comprises raw materials, by weight, including 4.3% of a water retaining agent (2-acrylamide-2-methylpropanesulfonic acid copolymer AMPS), 3.6% of a suspending agent (sepiolite powder), 19.9% ​​of a solidifying material (crystalline glassy tuff powder), 0.2% of a regulator (sodium hydroxide) and the remainder of water. The solidifiable inorganic plugging agent for fracture leakage is obtained by the following method: a required amount of a water retaining agent and a regulator are added to a required amount of water and stirred evenly, and then a required amount of a suspending agent and a solidifying material are added and stirred evenly, thereby obtaining the solidifiable inorganic plugging agent for fracture leakage.

[0027] Embodiment 8: The solidifiable inorganic plugging agent for fracture leakage comprises raw materials, by weight, of 4.7% water retaining agent (2-acrylamide-2-methylpropanesulfonic acid copolymer AMPS), 4.2% suspending agent (vermiculite powder), 12.6% consolidating material (crystalline glassy tuff powder), 0.5% regulator (sodium hydroxide) and the remainder of water. The solidifiable inorganic plugging agent for fracture leakage is obtained by the following method: a required amount of water retaining agent and regulator are added to a required amount of water and stirred evenly, and then a required amount of suspending agent and consolidating material are added and stirred evenly, thereby obtaining the solidifiable inorganic plugging agent for fracture leakage.

[0028] Compared with the existing cement-solidified plugging agents, the present invention has the following beneficial effects: Firstly, the particles of the solidifiable inorganic plugging agent for fracture leakage of the present invention are micron-sized, which can easily enter the leakage channel and space, and there is no problem of sealing and re-leakage; and its density is low, which can be equal to the density of drilling fluid, and there is no possibility of being easily blocked in the wellbore; Secondly, the solidifiable inorganic plugging agent for fracture leakage of the present invention has a large static shear force, is easy to be retained in the leakage channel, and does not have the risk of flowing to the far well area; and has a strong water retention capacity and strong anti-dispersion ability, can solidify at the required time, and does not have the possibility of plugging failure caused by prolonged solidification time; Thirdly, the solidifiable inorganic plugging agent for fracture leakage of the present invention can solidify itself and can be bonded with the formation at the same time. Once the plugging is successful, there is no risk of leakage again. Moreover, its compressive strength is low after solidification, and there is no problem of drilling a new wellbore when drilling the plug, thus avoiding the problem of well collapse and drill jamming caused by drilling a new wellbore. Existing drilling equipment can be used for construction without the need for additional construction equipment.

[0029] Embodiment 9: Under stirring, add 23.5g of water retaining agent (2-acrylamide-2-methylpropanesulfonic acid copolymer AMPS) and 2.5g of regulator (sodium hydroxide) to 360g of water and stir for 5 minutes. Then add 21g of suspending agent (sepiolite powder) and 99.5g of consolidating material (crystalline glass tuff powder) and stir for 5 minutes to obtain a solidifiable inorganic plugging agent for fracture leakage.

[0030] Comparative Example 1: At a stirring speed of 4000 r / min, 700 g of oil well cement was added to 308 g of water within 15 seconds, and then the stirring speed was increased to 12000 r / min and stirred for 35 seconds to obtain a G-grade oil well cement slurry.

[0031] Comparative Example 2: Under stirring, 20g of type A bridging material and 80g of type B bridging material were added to 400g of base slurry (400g of distilled water + 0.6g of anhydrous sodium carbonate + 20g of bentonite) and stirred to obtain a bridging plugging slurry. The type A bridging material is a thermosetting resin particle with a particle size of 3mm to 10mm, and the type B bridging material is a hollow spherical thermosetting resin particle with a particle size of 1mm to 6mm.

[0032] Example 10: Evaluation of mechanical properties of the solidifiable inorganic plugging agent for fracture leakage of the present invention Test 1: Density test Test method: The density of the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention was measured using a drilling fluid densitometer. Meanwhile, the G-grade oil well cement slurry obtained in Comparative Example 1 was used as a control.

[0033] Test results: As shown in Table 1, it can be seen from Table 1 that the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention is lower than that of G-grade oil well cement slurry, indicating that when plugging on site, the liquid column pressure formed by the solidifiable inorganic plugging agent for fracture leakage of the present invention in the wellbore is much lower than that of G-grade oil well cement slurry, and it is easier to stay in the wellbore, which is more conducive to successful plugging.

[0034] Test 2: Static shear test Test method: The static shear force of the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention is measured by a six-speed rotary viscometer, and at the same time, the G-grade oil well cement slurry obtained in Comparative Example 1 is used as a control. The specific method is to inject the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention and the G-grade oil well cement slurry into the sample cup of the rotary viscometer, and inject the height to the scale line, place the sample cup on the viscometer cup holder, adjust the cup holder height until the liquid level in the sample cup is level with the scale line on the rotor, start the rotary viscometer, rotate the rotor at a high speed (600r / min) to stir the liquid for 1 minute, and then let it stand for 10s and 10min respectively, measure the 3r / min reading, and divide the reading by 2 to obtain the static shear force of the liquid, that is, the initial shear force and the final shear force.

[0035] Test results: As shown in Table 2, it can be seen from Table 2 that the solidifiable inorganic plugging agent for fracture leakage of the present invention has not only a larger static shear force than the G-grade oil well cement slurry, but also a relatively close initial shear force and final shear force, indicating that in the on-site plugging construction, once the flow rate decreases, the static shear force of the solidifiable inorganic plugging agent for fracture leakage increases rapidly, and the flow resistance increases, which is conducive to the solidifiable inorganic plugging agent for fracture leakage being retained in the leakage channel. The G-grade oil well cement slurry does not have this characteristic.

[0036] Test 3: Compressive strength test Test method: The compressive strength of the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention after curing in a water bath at normal pressure / 52°C for 24 hours was tested using a compressive strength tester. At the same time, the G-grade oil well cement slurry obtained in Comparative Example 1 was used as a control. The specific method is to load the solidifiable inorganic plugging agent for fracture leakage of the present invention and the G-grade oil well cement slurry into a 50.8mm×50.8mm×50.8mm cubic test mold according to the specification, put it into a water bath at normal pressure / 52°C for curing for 24 hours, then take it out, cool it to room temperature in the water bath, wipe off the surface oil, and place it on the support block of the compressive strength tester. For the solidifiable inorganic plugging agent for fracture leakage, the loading rate of the tester is 17.9kN / min, and for the G-grade oil well cement slurry, the loading rate of the tester is 71.7kN / min. The compressive strength value can be read when the sample is destroyed, accurate to 0.1MPa.

[0037] Test results: As shown in Table 3, it can be seen from Table 3 that the compressive strength of the solidifiable inorganic plugging agent for fracture leakage of the present invention is much lower than that of G-grade oil well cement slurry and lower than the compressive strength of formation rock. Therefore, after the solidifiable inorganic plugging agent for fracture leakage of the present invention is used for plugging the inclined well section and drilling plugging, the drill bit will always drill along the original wellbore and will not drill out a new wellbore. Even if the plugging agent solidified body is left at the wellbore expansion, it will continue to drill and vibrate and fall into the wellbore, and it will be crushed by the drill tool and will not cause the drill to get stuck. However, due to the high compressive strength of G-grade oil well cement slurry, it is easy to drill out a new wellbore and drop blocks and get stuck.

[0038] Test 4: Anti-dispersion test Test method: Pour the solidifiable inorganic plugging agent for fracture leakage prepared in Example 9 of the present invention and the G-grade oil well cement slurry into a beaker filled with clean water, observe whether the clean water becomes turbid, and observe the accumulation state of the solidifiable inorganic plugging agent for fracture leakage and the G-grade oil well cement slurry at the bottom of the beaker after 5 minutes.

[0039] Test results: When the solidifiable inorganic plugging agent for fracture leakage of the present invention is poured into clean water, the water remains clear, is not dispersed, and does not clump together. After standing for 5 minutes, the state remains unchanged. However, when G-grade oil well cement slurry is poured into clean water, the water immediately becomes turbid, indicating that the cement slurry has been dispersed by water. After standing for 5 minutes, most of the cement particles settle to the bottom of the beaker, and some fine particles are still suspended in the water. This phenomenon corresponds to the scene, that is, the solidifiable inorganic plugging agent for fracture leakage of the present invention will not be dispersed in the leakage channel, and can be solidified according to the designed time, which is conducive to achieving the purpose of plugging. However, G-grade oil well cement slurry is easily dispersed and cannot be solidified within the designed time, so the plugging success rate is low. In short, the solidifiable inorganic plugging agent for fracture leakage of the present invention has good anti-dispersion property.

[0040] Test 5: Pressure bearing capacity test Test method: Inject the solidifiable inorganic plugging agent for crack leakage prepared in Example 9 of the present invention and the bridging plugging agent prepared in Comparative Example 2 into 4-2mm and 5-2mm seam pipes with a syringe, put them into a constant temperature water bath, and adjust to the experimental temperature of 75°C for curing. Put the seam pipe after the water bath into the CL-Ⅱ high temperature and high pressure dynamic plugging instrument for crack sealing experiment. Fill the kettle with 2300ml of clean water. Start the experiment after the preparation work is done; start from 1MPa, stabilize the pressure for 5min, and then pressurize to 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, and 7MPa in turn. Maintain the pressure for 5min each time, and the system automatically records the data. Then, according to the maximum pressure value obtained, pressurize to the maximum pressure value in the previous way, stabilize the pressure for 5min, and then conduct a reverse pressure test.

[0041] Test results: As shown in Table 4, it can be seen from Table 4 that the pressure bearing capacity of the solidifiable inorganic plugging agent for fracture leakage of the present invention is higher than that of the bridging plugging slurry, and the maximum pressure bearing capacity can reach 7MPa. At the same time, compared with the bridging plugging slurry, the solidifiable inorganic plugging agent for fracture leakage of the present invention is not prone to re-leakage, and the plugging effect is better.

[0042] In summary, the solidifiable inorganic plugging agent for fracture leakage of the present invention can easily enter the leakage channel and space, has low density, large static shear force, strong water retention capacity, and can solidify itself. Once the plugging is successful, there is no risk of re-leakage. At the same time, its compressive strength after solidification is low, and there is no problem of drilling a new wellbore when drilling the plug, thus avoiding the problem of well collapse and drill jamming caused by drilling a new wellbore.

[0043] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A solidifiable inorganic plugging agent for fracture leakage, characterized in that The raw materials include 4% to 5% of a water retaining agent, 3.5% to 4.5% of a suspending agent, 10% to 20% of a solidifying material, 0.1% to 0.5% of a regulator and the balance of water by weight.

2. The solidifiable inorganic plugging agent for fracture leakage according to claim 1, characterized in that The water retaining agent is 2-acrylamide-2-methylpropanesulfonic acid copolymer.

3. The solidifiable inorganic plugging agent for fracture leakage according to claim 1 or 2, characterized in that The suspending agent is one or more of sepiolite powder, vermiculite powder and basalt fiber.

4. The solidifiable inorganic plugging agent for fracture leakage according to any one of claims 1 to 3, characterized in that The consolidating material is crystalline glassy tuff powder with a particle size of 1000 mesh to 1200 mesh.

5. The solidifiable inorganic plugging agent for fracture leakage according to any one of claims 1 to 4, characterized in that The regulator is sodium hydroxide.

6. The solidifiable inorganic plugging agent for fracture leakage according to any one of claims 1 to 5, characterized in that The method is as follows: add the required amount of water retaining agent and regulator to the required amount of water and stir evenly, then add the required amount of suspending agent and consolidating material and stir evenly to obtain a solidifiable inorganic plugging agent for fracture leakage.

7. The method for preparing a solidifiable inorganic plugging agent for fracture leakage according to any one of claims 1 to 5, characterized in that The method is as follows: add the required amount of water retaining agent and regulator to the required amount of water and stir evenly, then add the required amount of suspending agent and consolidating material and stir evenly to obtain a solidifiable inorganic plugging agent for fracture leakage.